Environmental Noise from Underwater Explosions and the Impact of the Seabed on the Received Levels - Soloway, Alexander (My University, 2018)
In the following work measurements of underwater explosions from three experimental sites area presented and compared. The goals of this work are to present the measurements of small underwater explosions (charges weighing between 0.5 kg and 20 kg) with an emphasis on the metrics commonly used to describe environmental noise including the peak pressure and the SEL. These data are provided within the context of the measurement environments, the seabed in particular, so that they can be more effectively utilized by both researchers and policy makers for studying environmental noise and in the development of mitigation measures to protect marine life from harmful noise levels.
Thesis (Ph.D.)--University of Washington, 2018
Keywords: Explosion; Noise; Propagation; Scholte Wave; Shallow Water; Underwater Acoustics; Acoustics; Geophysics; Ocean engineering; Mechanical engineering